Brønsted Acidic Ionic Liquid Catalyzed Three-Component Friedel–Crafts Reaction for the Synthesis of Unsymmetrical Triarylmethanes - Rinkam, Suttida; Senapak, Warapong; Watchasit, Sarayut; Saeeng, Rungnapha; Sirion, Uthaiwan (Synlett, 2022)
A convenient and practical method for the synthesis of unsymmetrical triarylmethanes was demonstrated through a one-pot three-component double Friedel–Crafts reaction of various aliphatic, aromatic, or heteroaromatic aldehydes with N,N-dialkylanilines and indoles by using a Brønsted acidic ionic liquid as the catalyst. This method was successfully applied under metal- and solvent-free conditions at 80 °C, affording the corresponding unsymmetrical triarylmethane products in moderate to high yields from a broad range of substrates. In addition, the mechanism of this reaction was studied by quantitative NMR analysis.
Keywords: triarylmethanes; diarylmethylindoles; Friedel–Crafts reaction; Brønsted acid; ionic liquid; metal-free conditions